Determinan Kinerja Auditor pada Inspektorat Provinsi Riau - arini; Arini, Arini (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
This study aims to determine whether there is Integrity, objectivity, and Confidentiality on Auditor Performance at the Inspectorate of Riau Province. This research will be conducted at the Inspectorate of Riau Province. The research approach uses quantitative with primary data sources. The population and sample are all auditors in the Provincial Inspectorate office. Data analysis using multiple linear regression with SPSS 23. The results of statistical testing show that Integrity, Objectivity, and Confidentiality have a significant effect on Auditor Performance.